Pembiayaan Musyārakah Perspektif Fatwa DSN-MUI : Studi Di Kspps Melati Cabang Kertek Wonosobo - Fatimah, Siti (At-Ta’awun: Jurnal Mu’amalah dan Hukum Islam, 2023)
This research was conducted at KSPPS Melati Kertek Branch with the aim of finding out the implementation of the musyārakah financing agreement carried out by KSPPS Melati Kertek Branch and the suitability of the implementation of musyārakah financing with the DSN-MUI fatwa No.08/IV/2000 concerning musyārakah. The results of the discussion of this thesis show that the practice of musyārakah financing at KSPPS Melati Kertek Branch is in accordance with the DSN-MUI Fatwa in the aspect of ijab qobul, contracting parties, the object of the contract in the form of capital but is not in accordance with the aspect of profits and losses. Profit sharing or profit sharing at KSPPS Melati Kertek Branch is determined based on a percentage of the amount of financing and profit sharing has been determined at the beginning with a fixed nominal amount. On the other hand, KSPPS also takes advantage of the administrative costs, the larger the financing, the greater the administrative costs. Meanwhile, the distribution of losses is not based on the proportion of each individual's capital, which means it is not known how much capital the customer himself spent in his business.